P583 Real-life efficacy and safety of Ustekinumab as second- or third-line therapy in Crohn's disease: results from a large Italian cohort study. (27th May 2021) - Mocci, G; Cuomo, A; Allegretta, L; Aragona, G; Colucci, R; Della Valle, N; Ferronato, A; Forti, G; Gaiani, F; Graziani, M G; Lorenzetti, R; Luzza, F; et al.
Abstract: Background: Ustekinumab (UST) is an anti-IL12/23 antibody for the treatment of Crohn's Disease (CD). The aim of this study was to compare the efficacy and safety of UST in a large population-based cohort of CD patients who failed previous treatment with other biologics Methods: 194 CD patients (108 males and 86 females, mean age 48 years (range 38–58 years) were retrospectively reviewed. 147 patients were already treated with anti-TNFα (75.8%), and 47 (24.2%) patients were already treated with anti-TNFα and vedolizumab. Concomitant treatment with steroids was present in 177 (91.2%) patients Results: At week 12, clinical remission was achieved in 146 (75.2%) patients. After a mean follow-up of 6 months, clinical remission was maintained in 135 (69.6%) patients; at that time, mucosal healing was assessed in 62 (31.9%) patients, and it was achieved in 33 (53.2) patients. Three (1.5%) patients were submitted to surgery. Steroid-free remission was achieved in 115 (59.3%) patients. Both serum C-Reactive Protein and Fecal Calprotectin (FC) levels were significantly reduced with respect to baseline levels during follow-up. A logistic regression, UST therapy as thirdline therapy (after both anti-TNFα and vedolizumab), FC >200 μg/g, and HBI ≥8 were significantly associated with lack of remission. Adverse events occurred in 5 (2.6%) patients, and four of them required suspension of treatment Conclusion: Ustekinumab seemed to be really effective and safe in CD patients unresponsive to other biologic treatments, especially when used as second-line treatment.